A Bibliometric Analysis of Ophthalmology Resident Research Productivity in the United States - Huang, Austin; Kim, Sarah; Zhu, Harrison; Pathare, Nihar; Ooi, Xin Yee; Kirby, R. Parker; Yoon, Stephen P.; Al-Mohtaseb, Zaina (Journal of Academic Ophthalmology, 2022)
Background The extent and impact of ophthalmology resident scholarly output is not well known. The authors aim to quantify scholarly activity of ophthalmology residents during residency and assess what factors may be associated with greater research productivity of these residents.Material and Methods Ophthalmology residents who graduated in 2021 were identified from their respective program Web sites. Bibliometric data published by these residents between the beginning of their postgraduate year 2 (July 1, 2018) until 3 months after graduation (September 30, 2021) were captured through searches via PubMed, Scopus, and Google Scholar. The association of the following factors with greater research productivity numbers was analyzed: residency tier, medical school rank, sex, doctorate degree, type of medical degree, and international medical graduate status.Results We found 418 ophthalmology residents from 98 residency programs. These residents published a mean (±standard deviation [SD]) number of 2.68 ± 3.81 peer-reviewed publications, 2.39 ± 3.40 ophthalmology-related publications, and 1.18 ± 1.96 first-author publications each. The mean (±SD) Hirsch index (h-index) for this cohort was 0.79 ± 1.17. Upon multivariate analysis, we discovered significant correlations between both residency tier and medical school rank and all bibliometric variables assessed. Pairwise comparisons revealed that residents from higher tier programs had greater research productivity numbers than those from lower tier programs.Conclusion We obtained bibliometric standards for ophthalmology residents on a national scale. Residents who graduated from higher-ranked residency programs and medical schools possessed higher h-indices and published more peer-reviewed publications, ophthalmology-related articles, and first-author publications.
Keywords: ophthalmology residency; bibliometric analysis; research productivity; h-index